2017
DOI: 10.1159/000479075
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Concomitant Systemic Cancer is Not Associated with Worse Functional Long-Term Outcome in Patients with Intracerebral Hemorrhage

Abstract: Background: Data on clinical characteristics and outcome of patients with intracerebral hemorrhage (ICH) and concomitant systemic cancer disease are very limited. Methods: Nine hundred and seventy three consecutive primary ICH patients were analyzed using our prospective institutional registry over a period of 9 years (2006-2014). We compared clinical and radiological parameters as well as outcome - scored using the modified Rankin Scale (mRS) and analyzed in a dichotomized fashion as favorable outcome (mRS = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Detailed information and methods of the multicenter RETRACE program (part 1 recruited patients from 1 January 2006 until 31 December 2010 (NCT01829581) and part 2 from 1 January 2011 until 31 December 2015 (NCT03093233)) and the prospective UKER-ICH registry (NCT03183167) have been published previously. [14][15][16][17][18] The study was approved by the local ethics committees and institutional review boards based on the central vote from Friedrich-Alexander-University Erlangen-Nuremberg, Germany (Re.No-4409 & 30_16B, 115_17B). Written consent was obtained by patients or legal representatives.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information and methods of the multicenter RETRACE program (part 1 recruited patients from 1 January 2006 until 31 December 2010 (NCT01829581) and part 2 from 1 January 2011 until 31 December 2015 (NCT03093233)) and the prospective UKER-ICH registry (NCT03183167) have been published previously. [14][15][16][17][18] The study was approved by the local ethics committees and institutional review boards based on the central vote from Friedrich-Alexander-University Erlangen-Nuremberg, Germany (Re.No-4409 & 30_16B, 115_17B). Written consent was obtained by patients or legal representatives.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown no difference in ICH patients with and without cancer with respect to in-hospital mortality, short- and long-term outcome, and the proportion of patients with favorable functional outcome over a period of 12 months after ICH. 20 , 85 A possible reason why additional cancer diagnosis did not impact long-term prognosis after ICH was likely the importance of the severity of the bleeding itself. 85 Other studies have shown, on the contrary, higher odds of death and lower odds of favorable discharge in ICH patients with cancer.…”
Section: Prognosis In Patients Having Both Cancer and Strokementioning
confidence: 99%
“…Detailed information and methods of the multicenter RE-TRACE program (part 1 recruited patients from January 1, 2006, until December 31, 2010 [NCT01829581] and part 2 from January 1, 2011, until December 31, 2015 [NCT03093233]) have been published previously [3,[12][13][14][15].…”
Section: Study Participantsmentioning
confidence: 99%
“…Demographic, clinical, and laboratory data were collected as previously described [12]. Medical history of arterial hypertension, diabetes mellitus, prior stroke, congestive heart failure, abnormal kidney, and premorbid modified Rankin Scale (mRS) were assessed [17].…”
Section: Data Acquisition and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation